MEMAHAMI KEBIJAKAN RENCANA TATA RUANG WILAYAH DI PROVINSI BANTEN - Baharuddin Thahir (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2023)
One of the causes of environmental problems such as natural disasters in many parts of Indonesia is land use violations. This study uses a qualitative descriptive method with an inductive approach. In addition, researchers conducted data analysis using two models of analysis, namely the qualitative descriptive strategy model and the qualitative control analysis strategy model. RTRW as a policy is analyzed based on Grindle's view that there are two main variables that influence policy implementation, namely: political content; and implementation environment. Meanwhile, from the point of view of regional planning, Rapoport shows that housing formation does not only consist of physical factors, but can also consist of various existing socio-cultural factors and not in a narrow sense. see spatial planning as a result of spatial planning. He stressed that regional planning is all about distributing community activities and activities to achieve pre-formulated goals. Through this article we conclude that regional utilization must be addressed with regional planning policies. But in practice, the municipal government faces obstacles. The local government is trying to keep the RTRW consistent with government guidelines and it appears that the RTRW guidelines are also included in the planning documents. The city government participates in the planning, implementation and monitoring processes to ensure consistency in the implementation of the RTRW at both the provincial and district/city levels